Myocardial infarction caused by coronary artery damage from blunt chest injury. Issue 4 (April 1987) - Pringle, S D; Davidson, K G
Abstract : A case is reported in which blunt chest injury caused an intimal tear in the left anterior descending coronary artery. Despite few external signs of injury the patient sustained a myocardial infarction resulting in life threatening arrhythmias and considerable left ventricular dysfunction.